Política comercial e política externa no Brasil: Uma análise da estratégia de negociaç\~ao comercial brasileira (1995-2010) - Ivan Tiago Machado Oliveira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This paper aims to understand and examine one of the domestic determinants of Brazilian foreign trade policy strategies from 1995 to 2010, focusing on the articulation of its trade policy with its foreign policy at large. Thus, the role of multilateralism and regionalism in Brazilian foreign policy is analyzed in order to identify and understand Brazil's trade negotiation strategies in the period under review. With this work, I try to shed light on the debate about domestic determinants of foreign trade policy in Brazil in recent decades, explaining the adoption of a three-tracks negotiating strategy, which combines the multilateral approach with a two-speed regionalism.
Keywords: F50; F13; F10; 330; foreign trade policy; Brazil; multilateralism; regionalism; Außenwirtschaftspolitik; Brasilien